Individual Therapeutic Singing Program for Vocal Quality and Depression in Parkinson’s Disease - Eun Young Han; Ji Young Yun; Hyun Ju Chong; Kyoung-Gyu Choi (Journal of Movement Disorders, 2018)
Objective Patients with Parkinson’s disease (PD) frequently experience depression associated with voice problems. Singing involves the use of similar muscles and the neural networks associated with vocal function and emotional response. The purpose of this study is to enhance vocal quality and depressive symptoms of patients with PD using individual singing program. Methods The Individual Therapeutic Singing Program for PD (ITSP-PD) was conducted by a certified music therapist. In total, nine PD patients with a subjective voice problem or depression participated in 6 sessions over 2 weeks. We measured the Maximum Phonation Time (MPT) via the Praat test, the Voice Handicap Index (VHI), the Voice-Related Quality of Life (V-RQOL) and the Geriatric Depression Scale (GDS). Results In total, 8 out of 9 patients completed all the sessions; 6 out of 8 patients participated in the follow-up test after 6 months. A statistically significant change in MPT (P = 0.011) was observed between the pre- and post-tests. The VHI (P = 0.035) and the GDS (P = 0.018) were significantly lower in the post-test. In the pre-, post-, and follow-up tests, the MPT (P = 0.030), V-RQOL (P = 0.008), and GDS (P = 0.009) were significantly changed. Conclusion The ITSP-PD based on neurological singing therapy for PD showed therapeutic possibility for vocal function and depression in patients with PD. Our findings suggest the need for a randomized study to examine the continuing positive effects of the ITSP-PD over a longer period of time.